Outcomes and complications of postoperative seroma cavities following soft-tissue sarcoma resection - Andryk, Logan M.; Neilson, John C.; Wooldridge, Adam N.; Hackbarth, Donald A.; Bedi, Meena; Baynes, Keith E.; LoGiudice, John A.; Slusarczyk, Sonia M.; King, David M. (Frontiers in Oncology, 2024)
Introduction Seroma development is a known complication following extremity and trunk soft-tissue sarcoma (STS) resection. The purpose of this study is to evaluate and characterize seroma outcomes and the development of associated complications. Methods A retrospective review of 123 patients who developed postoperative seromas following STS resection at a single institution was performed. Various patient and surgical factors were analyzed to determine their effect on overall seroma outcomes. Results 77/123 seromas (62.6%) were uncomplicated, 30/123 (24.4%) developed infection, and 16/123 (13.0%) were symptomatic and required aspiration or drainage for symptom relief at an average of 12.2 months postoperatively. 65/123 (52.8%) seromas resolved spontaneously at an average time of 12.41 months. Seromas in the lower extremity (p=0.028), surgical resection volume >864 cm3, (p=<0.001) and initial seroma volume >42 cm3 (p=<0.001) increased the likelihood of infection. 90% of infected seromas developed the infection within the first three months following initial resection. No seromas which were aspirated or drained ultimately developed an infection following these procedures, though 50% recurred. Discussion Most seromas following STS resection are uncomplicated and do not require intervention, though a large resection cavity >864 cm3 and a large seroma volume >42 cm3 are risk factors for complications.